The Content Analysis of the Postgraduate Thesis Focused on the Families of Individuals Diagnosed with Autism in the Field of Sports in Turkey from 2013 to 2023 - FIRAT, Zeynep; ZORBA , Erdal; GÜRSOY , Ali Rıza; ÖZANT , M. İnan (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2024)
The objective of this study is to uncover the content analysis of postgraduate theses focused on the families of individuals diagnosed with autism, specifically within the realm of sports in Turkey from 2013 to 2023. The search was conducted using the keywords autism, family, and parent in the national thesis center of the Council of Higher Education. The search was specifically focused on the topics of sports, physical activity, movement training, and exercise. The national database of the Council of Higher Education's thesis center was utilized as a tool for data collection. The analysis revealed that a total of 22 theses were written, comprising 17 master's theses and 5 doctoral theses. The analyses revealed that the minimum years for thesis writing were 2013, 2015, 2017, and 2020, while the maximum year was 2019. Furthermore, it was observed that the first study investigating the involvement of families of individuals with autism in sports, physical activity, movement training, and exercise was conducted in 2013 at the doctoral level and in 2015 at the master's degree level. When analyzing the theses published in both master's and doctoral fields, it is evident that male authors contribute more than female authors. The most commonly used research method is qualitative. Additionally, it is noteworthy that the majority of research advisors hold the title of professor. In terms of language, it is observed that in the master's field, only one thesis is written in English while the rest are in Turkish. Similarly, in the doctoral field, one thesis is written in English while the others are written in Turkish.